Surgical treatment of distant metastases of melanoma– a case report - Kycler, Witold; Łaski, Piotr; Porzegowski, Marek; Teresiak, Marek (Contemporary Oncology/Współczesna Onkologia, 2006)
We report the case of a patient initially and continually treated with surgery for stage IIB melanoma involving the skin in the lumbar region. We observed local recurrence and distal metastases in the lungs and in the brain. Our patient has survived without relapse for 9 years after the initial diagnosis, 5 years after the pulmonary tumor excision, 4 years after the last cerebral metastatic tumor excision. The patient has been further observed as an ambulatory treated outpatient. Till now we have not observed a metastatic disease. Surgical resection of distant metastasis is a treatment and diagnostic procedures associated with low mortality and good survival. The results of many retrospective studies demonstrate the benefit of surgical resection for advanced-stage melanoma. Patients with good prognostic features, carefully selected should be considered for curative resection regardless of the location of the disease.